The Impact of Cisplatin‐ or Non‐Cisplatin‐Containing Chemotherapy on Long‐Term and Conditional Survival of Patients with Advanced Urinary Tract Cancer. (1st April 2019) - Bamias, Aristotelis; Tzannis, Kimon; Bamia, Christina; Harshman, Lauren C.; Crabb, Simon; Plimack, Elizabeth R.; Pal, Sumanta; De Giorgi, Ugo; Ladoire, Sylvain; Theodore, Christine; Agarwal, Neeraj; Yu, Evan Y.; et al.
Abstract: Background: The impact of cisplatin use on long‐term survival of unselected patients with advanced urinary tract cancer (aUTC) has not been adequately investigated. We used a multinational database to study long‐term survival and the impact of treatment type in unselected patients with aUTC. Materials and Methods: A total of 1, 333 patients with aUTC (cT4bN0M0, cTanyN+M0, cTanyNanyM+), transitional‐cell, squamous, or adenocarcinoma histology who received systemic chemotherapy and had available survival data were selected. Long‐term survival was defined as alive at 3 years following initiation of first‐line chemotherapy. Conditional overall survival (COS) analysis was employed to study change in prognosis given time survived from initiation of first‐line chemotherapy. Results: Median follow‐up was 31.7 months. The combination of cisplatin use and cisplatin eligibility accurately predicted long‐term survival. Eligible patients treated with cisplatin conferred a 31.6% probability of 3‐year survival (95% confidence interval [CI]: 25.1–38.3), and 2‐year COS for patients surviving 3 years after initiation of cisplatin‐based chemotherapy was 83% (95% CI: 59.7–93.5). The respective probabilities for patients who were ineligible for cisplatin or not treated with cisplatin despite eligibility were 14% (95% CI: 10.8–17.6) and 49.3% (95% CI: 28.2–67.4). Two‐year COS remained significantly different between these two groups up to 3 years after chemotherapy initiation. Conclusion: Cisplatin‐based therapy was associated with the highest likelihood of long‐term survival in patients with aUTC and should be used in patients who fulfill the established eligibility criteria. Novel therapies are necessary to increase long‐term survival in cisplatin‐ineligible patients. Implications for Practice: Long‐term, disease‐free survival is possible in one in four eligible‐for‐cisplatin patients with advanced urinary tract cancer (aUTC) treated with cisplatin‐based combination chemotherapy. Therefore, deviations from eligibility criteria should be avoided. Consolidation surgery should be considered in responders. These data provide benchmarks for the study of novel therapies in aUTC. Abstract : Cisplatin‐based chemotherapy is the treatment of choice in advanced urinary tract cancer. This article reports the results of a study that used the Retrospective International Study of Cancers of the Urothelium database to study long‐term survival among patients with advanced urinary tract cancer treated with chemotherapy and evaluate the importance of cisplatin use in this context.